UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOLIK DAGING BUAH BUNI (Antidesma bunius (L.) Spreng) TERHADAP Staphylococcus aureus ATCC 25922 dan Escherichia coli ATCC 25923 - Brigitta Lynda Rakasiwi; C.J. Soegihardjo (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2014)
Abstract: The aim of the study was to determine the antibacterial activity of buni skin-pulpethanolic extract against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC25922. Profile of antibiotic resistance which is growing among Staphylococcus aureus andEscherichia coli need some exploration of antibacterial activity buni skin-pulp because thecontain of anthocyanin which has antibacterial activity. The research was purely experimentalresearch with randomized complete direct sampling design. The extraction method was done bymacerated in ethanol solvent. Tube tests and Thin Layer Chromatography (TLC) were used todetermine the content of the secondary metabolites substance in buni skin-pulp ethanolic extract.Antibacterial activity test was done by diffusion method, then followed with liquid dilutionmethod to determine the Minimum Inhibitory Concentration (MIC) and Minimum BactericidalConcentration (MBC). The antibacterial activity was evaluated based on the result of inhibitionzone diameter then analyzed with Kruskal-Wallis test followed with Mann-Whitney test.The results showed that the chemical substances of the buni skin-pulp ethanolic extract predictedwith TLC assay were phenolic, flavonoids, and anthocyanin compounds. The antibacterialactivity showed that the ethanolic extract only had antibacterial activity against Staphylococcusaureus ATCC 25923 with MIC and MBC values 30% and 33%, respectively.Keywords: antibacterial potency, buni skin-pulp, Staphylococcus aureus, Escherichia coli